2016
DOI: 10.1002/jsfa.7538
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin converting enzyme (ACE) inhibitory and antihypertensive activities of protein hydrolysate from meat of Kacang goat (Capra aegagrus hircus)

Abstract: Protein hydrolysate of Kacang goat meat produced by sequential digestion with endo-proteinase and protease complex has great potential as a functional ingredient, particularly as an antihypertensive agent. © 2015 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 31 publications
0
19
2
Order By: Relevance
“…Among all the enzymes, pepsin, trypsin and pancreatin are generally used in research to simulate the gastrointestinal digestion in the hydrolysis of chicken breast muscle, duck, porcine muscle, bovine brisket muscle, venison muscle as well as some meat products such as dry-cured hams (Saiga et al, 2003;Escudero et al, 2012;. In the food industry, alcalase, flavourzyme and protamex are more widely used to produce peptides from duck, chicken, porcine protein, goat and bacon (Yanfeng & Li, 2006;Lee et al, 2010;Wang et al, 2015;Mirdhayati et al, 2016). A complex of proteases is also applied for the hydrolysis of meat protein including gelatin from duck and bovine skin (Kim et al, 2001;Lee et al, 2012).…”
Section: The Generation Of Bioactive Peptides From Meatmentioning
confidence: 99%
“…Among all the enzymes, pepsin, trypsin and pancreatin are generally used in research to simulate the gastrointestinal digestion in the hydrolysis of chicken breast muscle, duck, porcine muscle, bovine brisket muscle, venison muscle as well as some meat products such as dry-cured hams (Saiga et al, 2003;Escudero et al, 2012;. In the food industry, alcalase, flavourzyme and protamex are more widely used to produce peptides from duck, chicken, porcine protein, goat and bacon (Yanfeng & Li, 2006;Lee et al, 2010;Wang et al, 2015;Mirdhayati et al, 2016). A complex of proteases is also applied for the hydrolysis of meat protein including gelatin from duck and bovine skin (Kim et al, 2001;Lee et al, 2012).…”
Section: The Generation Of Bioactive Peptides From Meatmentioning
confidence: 99%
“…It may relate to the size and structure of the peptides resulting from the hydrolysis process. Mirdhayati, Hermanianto, Wijaya, Sajuthi, and Arihara, (2015) reported that a lower degree of hydrolysis lead the contained peptide in the hydrolysate to be larger so that the affinity towards the ACE active side becomes weak. The results of the analysis showed that the duration of hydrolysis had a significant effect on the ACE inhibitor (p <0.05).…”
Section: Characteristics Of Fish Protein Hydrolysatementioning
confidence: 99%
“…15-071). Change in SBP [10][11][12] is expressed as the difference in SBP before and after odor exposure. Data are expressed as mean ± standard error (SE).…”
Section: Quantification Of Potent Odorants In Maillard Reaction Samplmentioning
confidence: 99%